2015
DOI: 10.3390/sports3010021
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Review of Injuries in Rugby Union

Abstract: Rugby is a sport that is growing in popularity. A contact sport par excellence, it causes a significant number of injuries. In Rugby Union, there are 30 to 91 injuries per 1000 match hours. This epidemiological review of injuries incurred by rugby players mentions the position and type of injuries, the causes, time during the match and season in which they occur and the players' positions as well as the length of players' absences following the injury. OPEN ACCESSSports 2015, 3 22

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 34 publications
(101 reference statements)
4
20
1
4
Order By: Relevance
“…The most common injury to ankle in rugby player is lateral ankle sprain with 25% having anterior talofibular ligament tear (Sankey et al 2008;Kaux et al 2015). According to earlier reports, syndesmotic injuries, ankle sprains, degenerative injuries, Achilles tendon injuries and deltoid ligament sprains were the next most common match injuries (Sankey et al 2008).…”
Section: Rugbymentioning
confidence: 99%
“…The most common injury to ankle in rugby player is lateral ankle sprain with 25% having anterior talofibular ligament tear (Sankey et al 2008;Kaux et al 2015). According to earlier reports, syndesmotic injuries, ankle sprains, degenerative injuries, Achilles tendon injuries and deltoid ligament sprains were the next most common match injuries (Sankey et al 2008).…”
Section: Rugbymentioning
confidence: 99%
“…Previous studies have estimated that approximately 25% of sports injuries are ankle injuries (Fong et al, 2007). Even in rugby, which has a higher risk of injury than other sports, the ankle joint is cited as one of the sites with a high incidence of injury (Kaux et al, 2015;Yeomans et al, 2018). It was also reported that 17.5% of all injuries sustained by Japanese collegiate rugby players affected the ankle joint (Ogaki et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Injury rates have increased significantly in rugby union over the last decade [1]. The incidence of injury in the professional game has been found to be 218 and 6.1 injuries per 1000 h of competitive performance and practice respectively.…”
Section: Introductionmentioning
confidence: 99%